Regional Distribution of Female Labor Force in Turkey - Akman, Emine (Istanbul Univ Press, Istanbul Univ Rectorate, 2019)
The wage participation of women in the labor force was realized by the industrial revolution. The developing industry paved the way for women to sell their labor for wages. The most common problems faced by the female labor force are the low-wage employment in labor-intensive jobs and the lack of social security in the informal sector. In addition, the employer's gender discrimination is an important problem.The labor force participation of women in developed regions of Turkey is high, this case is lower than in developed regions. As a result, the female workforce has caused an uneven distribution at the regional level. Women have been limited in terms of women's identity in education, in return for their labor, in working life and in participating in social activities. Unfortunately, there are still traditional thinking systems. Women's role in this process of industrialization and urbanization by entering the process of social change has assumed new roles. Thus, women tried to gain economic freedom by entering the working life. In this study, regional distribution of female labor force was analyzed according to Statistical Region Units Classification (NUTS) Level 1. The main objective of the study is how the regional distribution of the female labor force in Turkey, clarifies the causes and the results are in line with the basic principles of geography. In addition, female employment, female labor force participation rates (LFPR) and factors affecting female labor force participation at regional level were discussed. The data obtained in this study on the regional distribution of the female labor force in Turkey Turkey Statistical Institute (TUIK) data are obtained from the official website. The reason why NUTS (Level 1) is taken as the basis in the regional classification is that there is a regional separation according to the provincial borders. In another classification, geographical region separation, healthy data could not be provided since not all provinces were located in one region.
1st Istanbul International Geography Congress -- JUN 20-22, 2019 -- Istanbul, TURKEY
Keywords: Labor Force; Employment; Labor Force Participation Rate